The immune response against cancer is modulated by stromal cell fibronectin - Lubosch, Alexander; Pitt, Lauren; Zöller, Caren; Wirth, Franziska; Exner, Tarik; Steigenberger, Barbara; Wabnitz, Guido H.; Schröder-Braunstein, Jutta; Nakchbandi, Inaam (Neoplasia, 2025)
Cancer-associated fibroblasts remain poorly understood, with some of them originating from the bone marrow. We therefore took advantage of the diversity of bone marrow stromal cells to shed light on how fibroblasts modulate cancer growth. In two murine cancer models, adding these fibroblasts to tumor cells resulted in smaller lesions. Suppression was enhanced by pretreatment with fibronectin, while genetic deletion of fibronectin in a small subpopulation of stromal cells expressing osterix/sp7 restored growth. The suppressive stromal population showed two more characteristics: the absence of CD31/pecam1 and CD105/endoglin. However, only a decrease in CD105/ENDOGLIN in melanoma patients translated in improved survival. Mechanistically, fibronectin or fibronectin fragments activate integrin α5β1 and TLR4 and increase chemokine production by stromal cells ultimately leading to enhanced recruitment and activity of Ly6G+ myeloid cells without T-cell involvement. This work thus characterizes a beneficial interaction between stromal cells and neutrophils enhancing the immune response against early cancer.
Online verfügbar: 30. Juni 2025
Gesehen am 18.11.2025